Studying cultures - Ochoa-Becker, Anna S.; Cherryholmes, Cleo H.; Manson, Gary (New York : Webster Division, McGraw-Hill, 1979)
A fourth grade textbook which discusses four subcultures: the Tasaday of of the Philippines, the Mossi of Upper Volta, the Aymara of Bolivia, and the Uzbeks of the Soviet Union.
Includes index.
Keywords: Ethnology -- Juvenile literature; Ethnology